Parents’ perception regarding the concerns, competencies and perspectives of involvement in non-formal activities - Coșarbă, Editha; Roman, Alina Felicia; Costin, Alina (Technium Social Sciences Journal, 2021)
This study aims to assess the perception of parents of primary school children about the concerns they have, the knowledge they have about their child’s skills. Starting from the educational and socializing function of the family (Jabbarova, 2020; Syamsuddin, 2021), we formulated the following research questions: What type of problems does a 7-11 years old child have to confront? According to parents, which are the necessary abilities a 7-11 year old child has to possess? How much do children participate in non-formal activities in their spare time? 62 participants completed a semi-structured questionnaire and participated in 10 interviews. The results reveal particularities of the reality of family life, such as the reduced time spent by parents with their children, the concern of parents for the time spent by the child in the online environment. Parents also reported the lack of interdisciplinary, non-formal, attractive programs and projects for children. The results indicate the focus of parents in the formation of memory skills and critical thinking and less on academic skills. Parents express concerns about spending their child’s time online but are confident that they can still handle this. The study actually describes some parents worried about many aspects of a child’s life, however they are not involved in parenting programs.